Current advances in the structural biology and molecular engineering of PETase - Liu, Fei; Wang, Tao; Yang, Wentao; Zhang, Yingkang; Gong, Yuming; Fan, Xinxin; Wang, Guocheng; Lu, Zhenhua; Wang, Jianmin (Frontiers in Bioengineering and Biotechnology, 2023)
Poly(ethylene terephthalate) (PET) is a highly useful synthetic polyester plastic that is widely used in daily life. However, the increase in postconsumer PET as plastic waste that is recalcitrant to biodegradation in landfills and the natural environment has raised worldwide concern.Currently, traditional PET recycling processes with thermomechanical or chemical methods also result in the deterioration of the mechanical properties of PET. Therefore, it is urgent to develop more efficient and green strategies to address this problem. Recently, a novel mesophilic PETdegrading enzyme (IsPETase) from Ideonella sakaiensis was found to streamline PET biodegradation at 30 ℃, albeit with a lower PET-degrading activity than chitinase or chitinase-like PET-degrading enzymes.Consequently, the molecular engineering of more efficient PETases is still required for further industrial applications. This review details current knowledge on IsPETase, MHETase, and IsPETase-like hydrolases, including the structures, ligand-protein interactions, and rational protein engineering for improved PET-degrading performance. In particular,